ANALISIS KINERJA PEMERINTAH DALAM IMPLEMENTASI URUSAN OTONOMI DAERAH DI DISTRIK BUGI KABUPATEN JAYAWIJAYA PROPINSI PAPUA - GOMBO, NURIANA; Mandey, Jantje; Dengo, Salmin (Sam Ratulangi University, 2015)
ABSTRACT :The purpose of this study was to determine the performance BugiJayawijaya Districtgovernment in the implementation of regional autonomy affairs.This study used qualitative methods. Government performance district views of three indicators ofeffectiveness, efficiency and responsiveness. The informants drawn from government elements BugiDistrict (the district chief and secretary of the district), an element of SKPD or UPT Regional Office inthe region of Bugi District, two village heads, and two community leaders / religious / traditional. Thesum of all the informants who were interviewed are as many as 8 people. Collecting data usinginterview techniques, while the analysis of data using qualitative analysis interactive model of Milesand Hubernann. The results showed: (1) the District government performance Bugi seen fromindicators of effectiveness is quite good but not optimal. (2) Performance Bugi seen from the Districtgovernment efficiency indicators are also quite good, but not maximized. (3) The District governmentperformance Bugi seen from the indicators of responsiveness is also quite good, but not maximized.Based on the results of these studies conclude that the government's performance Bugi District in theimplementation of regional autonomy affairs generally quite good, but not maximized seen fromindicators of effectiveness, efficiency, and responsiveness.Based on the results of the research, put forward some suggestions to improve performance BugiDistrict government in the implementation of regional autonomy affairs, as follows: (1) The DistrictGovernment should be allocated sufficient budget to finance programs and activities. (2) The provisionand improvement of infrastructure and facilities Bugi District government work needs to be done; and(3) Employee / Bugi District government officials should be increased, and the quality of humanresource / employee also needs to be enhanced through appropriate education and training.Keywords: Performance, District Government, the Regional Autonomy Affairs